Sports practice in leisure time and its role in enhancing team performance within economic institutions: A study on the Regional Directorate of Maintenance in El Oued - ben djadou bait, Redouane (sports creativity, 2025)
In the modern era, the world has witnessed several changes encompassing various economic, social, cultural, and sports sectors. The goal has been to overcome difficulties and create a safer, more stable, and advanced life, through the high-quality products produced in all aspects of life. One of the major negative outcomes of these changes is work-related stress, making recreation and practicing sports among the most important daily life requirements, especially during leisure time. Practicing sports in its modern educational form, with its organization and scientifically based rules, is an important field of modern education and a strong, effective element in preparing a good citizen by nurturing them and equipping them with various motor and psychological skills and physical abilities, enhancing the efficiency of the body's vital systems, activating social aspects in daily practices, and reducing individualistic behaviors. This is because God Almighty has blessed community and collective work, and Islam is a religion that adheres to the community as a life approach in all matters. This is most evident in its emphasis on the community in devotional rituals and practical life, due to the harmony, cohesion, and cooperation it fosters. The prophetic hadiths that urge Muslims to maintain cohesion, strengthen ties of cooperation, and work in the spirit of teamwork and as one body are numerous, including: - His saying, peace be upon him, 'The believer to another believer is like a solid building, each part strengthening the other.' - His saying, peace be upon him, 'The example of the believers in their affection, mercy, and compassion for one another is like a single body; when one part of it suffers, the rest of the body responds with sleeplessness and fever.' If collectivity is emphasized and recommended in legislation, it also becomes essential and necessary in many human activities, particularly those that require cooperation and collective effort through teamwork. The need for work teams has become a necessity to face various challenges and is no longer just an administrative 'luxury.' Individualistic and isolationist attitudes among individuals, departments, and units within administrations are no longer acceptable because economic, social, and service activities are fundamentally based on cooperation among individuals. The more successful teamwork is, the more successful administrations are in achieving their goals, and vice versa. Work teams are merely a manifestation of the interaction among individuals as a group and also embody the concept of collective work. Administrations with their different types of individuals have become in urgent need of relying on the concept of Work teams, as this approach harnesses mental capabilities and behavioral skills, and gathers the experiences, ideas, suggestions, and strengths of team members to make them more responsive to the challenges of a competitive environment. Work teams represent an important tool for achieving integration and balance between individual goals and institutional objectives, in addition to unifying individual efforts within a single collective framework and working in a team spirit. The social nature that characterizes sports practice, which predominates in various sporting competitions, instills in the individual discipline, loyalty, a sense of responsibility, and a love of cooperation. It also teaches adherence to the group, collective behavior, the establishment of good relationships between individuals and groups, and self-confidence during daily and professional tasks. Investing leisure time is considered one of the most important factors affecting the development of individuals' personalities and is one of the key issues that institutions and social bodies devote significant attention to. Numerous studies have addressed the importance of practicing sports during leisure time, such as the studies by Pasco, Biegel, Hermann, and Robaltz, all of which agreed that engaging in sports during leisure time is one of the most important factors.